Rare Earth Elements in Tropical Agricultural Soils: Assessing the Influence of Land Use, Parent Material, and Soil Properties - Castellano, Gabriel Ribeiro [UNESP]; dos Santos, Juliana Silveira; Zanatta, Melina Borges Teixeira [UNESP]; Alves, Rafael Souza Cruz [UNESP]; de Souza, Zigomar Menezes; Ribeiro, Milton Cesar [UNESP]; Menegário, Amauri Antonio [UNESP] (MDPI, 2025)
Rare earth elements (REEs) are emerging soil contaminants due to increasing fertilizer use, mining activities, and technological applications. However, few studies have assessed their concentrations in soils or associated environmental risks. Here, we evaluate the influence of land cover types (Eucalyptus plantation, forest, and pasture), parent material, and soil physicochemical properties (predictor variables) on REE content in the Brazilian Atlantic Forest and measure pseudo-total REE content using inductively coupled plasma mass spectrometry (ICP-MS). Differences in REE content across land cover types, parent materials, and soil properties were assessed using similarity and variance analyses (ANOSIM, ANOVA, and Kruskal–Wallis) followed by post hoc tests (Tukey HSD and Dunn’s). We used model selection based on the Akaike criterion (ΔAICc < 2) to determine the influence of predictor variables on REE content. Our results showed that parent materials (igneous and metamorphic rocks) were the best predictors, yielding plausible models (Adj R2 ≥ 0.3) for Y, δEu, and LaN/SaN. In contrast, Ca:Mg alone provided a plausible model (Adj R2 = 0.15) for δCe anomalies, while clay content (Adj R2 = 0.11) influenced the SaN/YbN ratio, though soil properties had weaker effects than parent materials. However, we found no evidence that Eucalyptus plantations or pastures under non-intensive management increase REE content in Brazilian Atlantic Forest soils.